The degree of concha bullosa pneumatization and its association with severity of deviated nasal septum in patients of southern region in Saudi Arabia - Mubarki, Musleh; Shamakhi, Radeif; Daghriri, Ramzi; Alzarei, Ali; Hakami, Khaled (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: To determine the degree of concha bullosa pneumatization and its association with deviated nasal septum in patients of southern region in Saudi Arabia. Methods: This study used a retrospective radiological design to analyze computed tomography scans of 117 patients aged between 18 and 80 years of southern region in Saudi Arabia were used in this study. Patients with altered anatomy (iatrogenic or pathological) were excluded, CT scans were analysed to determine. The degree of concha bullosa and its association with deviated nasal septum in patients of southern region in Saudi Arabia, and the correlation between them. Results: Forty percent (40%) cases were male and sixty percent (60%) were female. Concha bullosa (CB) were found in 17(14.5%) cases, of which 4 cases (23%) were bilateral and 13(76%) were unilateral. 7(53%) of unilateral cases were on right side, 6(47%) on left side. From all CB patients in this sample size, 15 (88%) cases have deviated nasal septum that range from mild to severe type whereas 2(12%) cases have no deviated nasal septum. Only 1 of those patients with severe deviated nasal septum has extensive type of concha bullosa. Conclusions: Our findings revealed that there is no relationship between degree of pneumatization of CB and severity of deviated nasal septum.